RIGHT POSSESSION PROBLEMS IN COLLECTING OF PROOFS OF THE LAWYER DEFENDER - м, Ермек Талантулы; Zhanybekov , Акынкожа Каленулы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
In this article it is considered theoretical problems independent activity of the lawyer defender in participation collecting of proofs. The problems concerning activity of lawyers in criminal trial, are investigated in recent years rather actively, at the same time by the author is noted that so far to research of the problems arising in the course of formation and realization by the lawyer defender of a legal position on criminal case.